How to Do Random Allocation (Randomization) - Kim, Jeehyoung; Shin, Wonshik (Clinics in orthopedic surgery, 2014)
To explain the concept and procedure of random allocation as used in a randomized controlled study. We explain the general concept of random allocation and demonstrate how to perform the procedure easily and how to report it in a paper.